Value in Marx: A Reading of the Grundrisse - Kutlu Tuncel (Felsefe Arkivi)
Marx’s concept of value has been subject to significant criticism. Robinson argues that the concept is awkward and obscure, as it is meant to explain the prices of commodities and thus must be a kind of price, but it is not. Consequently, Robinson holds that the concept of value makes no sense. Furthermore, according to Harvey, Marx in the Grundrisse confuses value with price. It seems to me that both Robinson’s criticism and Harvey’s exegesis are based on serious misunderstandings. In this article, I first unpack Marx’s criticism of Darimon’s proposal concerning time chits. The upshot is that, for Marx, production relations enjoy a priority, and a monetary reform like Darimon’s cannot fulfill the function of revolutionary change. So, time chits become a triviality. Second, I suggest a reconstruction of what I call Marx’s “nonconvergency thesis.” The thesis states that there is a supervenience between value and price. Marx says that Darimon is ignorant about this thesis, and his proposal relies on the delusion that the two are convergent. Therefore, I maintain that Harvey’s claim is misleading, as he overlooks the nonconvergency thesis articulated in the Grundrisse. And Robinson’s condemnation of the concept of value should be dismissed because her understanding is very much the same as Darimon’s, in that she ignores the two-layered ontological structure between value and price.